2011
DOI: 10.1002/eji.201041211
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency and adaptive‐like dynamics of human CD1 self‐reactive T cells

Abstract: CD1 molecules present lipid antigens to T cells. An intriguing subset of human T cells recognize CD1-expressing cells without deliberately added lipids. Frequency, subset distribution, clonal composition, naïve-to-memory dynamic transition of these CD1 selfreactive T cells remain largely unknown. By screening libraries of T-cell clones, generated from CD4 1 or CD4 À CD8 À double negative (DN) T cells sorted from the same donors, and by limiting dilution analysis, we find that the frequency of CD1 self-reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
154
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(167 citation statements)
references
References 36 publications
12
154
1
Order By: Relevance
“…Human CD1d-restricted type 1 and type 2 NKT, CD1b-restricted and CD1c-restricted T-cell clones, and mouse iNKT hybridomas were derived as described (21)(22)(23) and maintained according to standard procedures. Human monocytic THP-1 and C1R B cells were transfected with human CD1B, CD1C, and CD1D cDNAs alone or in combination with human CD1E cDNA, using the BCMGS-Neo and BCMGS-Hygro vectors (4).…”
Section: Methodsmentioning
confidence: 99%
“…Human CD1d-restricted type 1 and type 2 NKT, CD1b-restricted and CD1c-restricted T-cell clones, and mouse iNKT hybridomas were derived as described (21)(22)(23) and maintained according to standard procedures. Human monocytic THP-1 and C1R B cells were transfected with human CD1B, CD1C, and CD1D cDNAs alone or in combination with human CD1E cDNA, using the BCMGS-Neo and BCMGS-Hygro vectors (4).…”
Section: Methodsmentioning
confidence: 99%
“…While the involvement of peptide-reactive T cells has been well defined (12)(13)(14)(15), the role of lipid-reactive T cells in psoriasis remains largely unknown. Since psoriasis and cardiovascular disease are correlated with hyperlipidemia and recent studies have identified CD1-restricted self-lipid-reactive T cells in the blood or skin of humans (16)(17)(18)(19), we developed a new mouse model for the study of human CD1-restricted T cell responses to self-lipids in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…de Lalla et al (30) found that CD1c-reactive T cells are unexpectedly high to 66% of self-reactive T cell clones screened in circulating T cells. Due to the large amount of CD1c-restricted T cells in PBMCs, the repression of CD1c expression will consequently compromise T cell activity.…”
Section: Discussionmentioning
confidence: 99%